A Web-Based FSKTM FYP Management System - Arumugam, Sarvine; Abd Ishak, Suhaimi (Applied Information Technology And Computer Science, 2025)
The FSKTM FYP Management System (FFMS) is a web-based platform designed to streamline FSKTM final year project management for final year students. The system desires to resolve issues such as time-consuming manual task tracking, inefficient communication and delays in project administering. It offers features such as real-time progress tracking, automated deadline reminders, role-based access for students, supervisors and project coordinators and productive reporting mechanisms. The objective is to improve operational efficiency, enhance interactivity, and ensure timely project completion while addressing current project management challenges. The project advantages advanced technology to optimize processes, using a systematic approach with detailed user acceptance testing to ensure a reliable, error-free system. FFMS is developed to be scalable and customizable to meet the needs of various academic institutions, promoting better organization and performance. The system is expected to transform the management of final year projects, effecting data management more accessible, comprehensive and accurate.